QUALITY SERVICE ON PUBLIC SATISFACTION OF BPJS HEALTHCARE USERS - Deu, Fitriani; Tahir, Arifin; Isa, Rusli (Universitas Negeri Gorontalo, 2023)
The achievement of perfect service quality will promote the creation of community satisfaction because service quality is a means torealize community satisfaction. This study aims to determine the influence of service quality on public satisfaction of BPJS users partially or simultaneously at Kabila Public Health Center, Bone Bolango Regency. The research employed a quantitative method with a total of 50 respondents. Data were collected through questionnaire and analysed using a simple regression analysis with the aid of the SPSS 25 Microsoft Excel application. The findings demonstrated that the service quality variable has a positive, indicating that if the quality improves, and so public satisfaction will follow. The results of the coefficient of determination test obtained the R Square value of 0.630, meaning that the influence of the quality variable is 63%. Therefore, the overall quality variable has an influence of 63% on the satisfaction variable. Whereas, the remaining 37% is influenced by other variables such as awareness, regulation, organization, income, skill and ability, and service facilities. Partially, service quality has a predominant influence over community satisfaction.